134 Development of an evidence-based safer opioid prescribing toolkit for clinical care. (5th May 2020) - Losman, E; Ngo, Q; Rooker, A; Roche, J; DeLaCruz, J; Moore, A; Walton, MA; Cunningham, R; Carter, PM
Abstract : Statement-of-Purpose: Despite a 30% reduction nationwide in new opioid prescriptions since 2012, prescription opioid overprescribing, as well as opioid misuse and overdose remain significant U.S. public health issues. To address a deficit in educational resources/tools for clinical providers and their patients, the Injury Prevention Center (UM-IPC), in partnership with the Department of Health and Human Services (MDHHS), created the Michigan Safer Opioid Prescribing Toolkit – a comprehensive, evidence-based, on-line resource. Methods/Approach: A needs assessment was conducted, identifying knowledge/skills gaps among primary care providers across the state. Utilizing results, a comprehensive review of publicly available opioid prescribing resources and systematic literature review to identify up-to-date recommendations was conducted in key areas. Provider- and patient-focused educational content and resources were identified/curated from existing sources or newly developed for the toolkit. Resources were reviewed by expert researchers/clinicians for accuracy and by practicing primary care clinicians for usability and applicability/relevance. Results: Toolkit resources were developed across seven domains, including background resources on pain and pain management (managing acute/chronic pain, reducing stigma), management strategies for chronic opioid use and opioid use disorders (screening tools, naloxone, medication-assisted treatment), non-opioid/non-pharmacological pain management, opioid pain management (prescribing/tapering guidelines), prescribing laws (PDMPs, legal resources), just-in-time resources (clinical decision flowcharts, assessment tools, safe storage/safe disposal), and special populations (adolescents, LGBTQ, pregnant women, veterans, etc.). In the first two weeks since the November 2019 launch (michmed.org/optoolkit), website reach has included 1, 846 unique visitors, suggesting high engagement with toolkit content. Conclusions: Development/dissemination of a just-in-time toolkit to guide evidence-based primary care pain management (i.e., safer opioid prescribing), harm reduction, and opioid use disorder treatment/linkage to care has potential for broad public health and clinical impact in addressing the opioid epidemic. Significance/Contributions to Injury/Violence Prevention: This toolkit is one of the first fully online, comprehensive, evidence-based clinical resources to address the opioid epidemic.